An Adaptive Systematic Lossy Error Protection Scheme for Broadcast Applications Based on Frequency Filtering and Unequal Picture Protection. (15th October 2008) - Ramon, Marie; Coudoux, François-Xavier; Gazalet, Marc
Abstract : Systematic lossy error protection (SLEP) is a robust error resilient mechanism based on principles of Wyner-Ziv (WZ) coding for video transmission over error-prone networks. In an SLEP scheme, the video bitstream is separated into two parts: a systematic part consisting of a video sequence transmitted without channel coding, and additional information consisting of a WZ supplementary stream. This paper presents an adaptive SLEP scheme in which the WZ stream is obtained by frequency filtering in the transform domain. Additionally, error resilience varies adaptively depending on the characteristics of compressed video. We show that the proposed SLEP architecture achieves graceful degradation of reconstructed video quality in the presence of increasing transmission errors. Moreover, it provides good performances in terms of error protection as well as reconstructed video quality if compared to solutions based on coarser quantization, while offering an interesting embedded scheme to apply digital video format conversion.